(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2017)
تهدف هذه الدراسة إلى بيان قدرة الشركات السورية على تحسين أدائها التسويقي من خلال تبني مفهوم المحاسبة الخضراء وأثر ذلك على الحصة السوقية, فركزت الدراسة على المعرفة البيئية بمقومات ومعوقات تطبيق المحاسبة الخضراء ومدى تأثيرها على الأداء التسويقي للشركة. وتم ذلك باستخدام المنهج الوصفي من خلال تصميم استبانه وتوزيعها على العاملين في شركة بانياس لتكرير النفط, كما تم تحليل البيانات باستخدام البرنامج الإحصائي SPSS , وتوصل البحث إلى أن المعرفة البيئية لدى العاملين ليست بالمستوى المطلوب, وهذا ما يعيق تطبيق المحاسبة الخضراء بمفهومها الأكاديمي بشكل أساس, بالإضافة إلى وجود الكثير من المعوقات التي حدت من النجاح في تطبيق المحاسبة الخضراء وبدوره انعكس سلباً على الأداء التسويقي للشركة. This study aims to clarify the ability of Syrian companies to improve their performance through adoption of green accounting as a marketing concept and its impact on market share. The study focused on the components and obstacles of environmental knowledge for application of green accounting and its impact on the marketing performance of the company. The researcher used the descriptive approach in the research community (Banias Oil Refining Company), using a survey that has been distributed amongst workers in the company, then the researcher analyzed the survey results by the Statistical Package for the Social Sciences (SPSS). The research concluded the following findings: Environmental knowledge among workers is not at the required level, and this is what hampers the application of green accounting in the academic concept Basically, in addition to having a lot of obstacles that have limited the success in the application of green accounting and that reflected in turn on the marketing performance of the company.